A Comprehensive Review on The Effects of Olestra - ELANGKOVAN, DENESH RAJ; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Olestra is known as a fat substitute or chemically derived as sucrose polyester. It’s also known by its brand name Olean. It does not add on calories or cholesterol to the product. It’s also used in food preparation such as potato chips. Originally it's been approved by The Food and Drug Admiration [FDA] for the replacement of fats and oil. It is majorly used to condition dough, as one of many ingredients and as flavouring agent in baking and frying or even generally used as dressing for salad. Olestra has zero calories opted for fat replacement in the various preparations of savory snacks. Nowadays, coronary heart diseases [CHD] are commonly known worldwide and research has proven that the type of our diet contributes to the elevation of blood cholesterol depending on the amount and type of fats consumed. Besides CHD, consumption of fats also accords the growth of cancer like breast, colon and prostate. However, Olestra has a few major drawbacks in playing its role in the human system as it is not absorbed into the human digestive system and henceforth not supplying any nutrition nor energy. Besides that, when consumed with other lipophilic dietary supplements, the absorption of Olestra is affected. This review article highlights in detail about olestra.